Mapping User Dissatisfaction in Mobile Banking Applications Using Ensemble Clustering LDA and LSA - Kusumaningtyas, Kartikadyota; Lahitani, Alfirna Rizqi; Dwijayanti, Irmma; Habibi, Muhammad (Universitas Multimedia Nusantara, 2025)
Mobile banking has become one of the most popular choices compared to other online banking services. Google Play Store is an online application store platform provides a review section for users to give ratings and comments on the applications they use. Positive reviews typically contain good experiences that reflect user satisfaction, while negative reviews usually contain poor experiences that indicate complaints and user dissatisfaction. However, Google Play Store does not yet have a feature to automatically map the main topics in both positive and negative reviews. Specifically for negative reviews, this can make it difficult for developers to understand the root problems and take appropriate corrective actions. In some situations, negative reviews need to be handled more quickly. Slow handling of negative reviews can impact the decline in reputation and customer loyalty. This research aims to identify user dissatisfaction topics based on negative reviews of several popular mobile banking applications in Indonesia, namely BCA Mobile and BRImo.